Proline-catalyzed asymmetric -amination in the synthesis of bioactive molecules - Kumar, Pradeep; Sharma, Brijesh M. (Synlett, 2018)
The direct -amination of carbonyl compounds using organocatalysts represents a powerful and atom-economical tool for asymmetric C-N bond formation. We describe a complete account of -functionalization of carbonyl compounds, through iterative sequential -aminoxylation/amination using electrophilic O and N sources, as well as sequential -amination/HWE reaction for enantio- and diastereoselective synthesis of both syn - and anti -1,3-aminoalcohols and 1,3-diamines. Additionally this protocol is further extended for the easy construction of alkaloids such as indolizidine, pyrrolizidine, and quinolizidine fused-ring systems just by tuning the chain length of the aldehyde used as a starting material. This methodology provides further scope to extrapolate it for a variety of naturally occurring hydroxylated monocyclic and fused bicyclic pyrrolidine and piperidine based alkaloids such as lentiginosine, epi -lentiginosine, dihydroxypyrrolizidine, (+)-deoxoprosophylline and (-)-deoxoprosopinine alkaloids. Furthermore, we have also uncovered proline-catalyzed anti -selectivity for the synthesis of 1,2-amino alcohols in -amination of aldehyde and one-pot indium-mediated Barbier type allylation of -hydrazino aldehydes to accomplish the total synthesis of clavaminols, sphinganine and spisulosine with reduced number of steps and with high overall yields. 1 Introduction 2 Application in the Total Synthesis of Alkaloids 3 Conclusion